Single-cell transcriptomics reveals immune response of intestinal cell types to viral infection - Triana, Sergio; Stanifer, Megan; Metz Zumarán, Camila; Shahraz, Mohammed; Mukenhirn, Markus; Kee, Carmon; Serger, Clara; Koschny, Ronald; Ordonez-Rueda, Diana; Paulsen, Malte; Benes, Vladimir; Boulant, Steeve; et al. (Molecular systems biology, 2021)
Human intestinal epithelial cells form a primary barrier protecting us from pathogens, yet only limited knowledge is available about individual contribution of each cell type to mounting an immune response against infection. Here, we developed a framework combining single-cell RNA-Seq and highly multiplex RNA FISH and applied it to human intestinal organoids infected with human astrovirus, a model human enteric virus. We found that interferon controls the infection and that astrovirus infects all major cell types and lineages and induces expression of the cell proliferation marker MKI67. Intriguingly, each intestinal epithelial cell lineage exhibits a unique basal expression of interferon-stimulated genes and, upon astrovirus infection, undergoes an antiviral transcriptional reprogramming by upregulating distinct sets of interferon-stimulated genes. These findings suggest that in the human intestinal epithelium, each cell lineage plays a unique role in resolving virus infection. Our framework is applicable to other organoids and viruses, opening new avenues to unravel roles of individual cell types in viral pathogenesis.
Gesehen am 06.10.2021